Richard-Jorba, Rodolfo, Eduardo Pérez Romagnoli, Patricia Barrio e Inés Sanjurjo, La región vitivinícola argentina. Transformaciones del territorio, la economía y la sociedad 1870-1914, Buenos Aires, UNQ, 2006 (296 págs.) - JUAN PABLO FASANO (H-Industri@)
Richard-Jorba, Rodolfo, Eduardo Pérez Romagnoli, Patricia Barrio e Inés Sanjurjo, La región vitivinícola argentina. Transformaciones del territorio, la economía y la sociedad 1870-1914, Buenos Aires, UNQ, 2006 (296 págs.)